Teachers’ Perceptions of Principals’ Leadership Styles in Enhancing Professional Competence - Wahyudi; Juhri Abdul Mu’in; Muhammad Badrun; Fatqul Hajar Aswad (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
The leadership style of a principal has a significant influence on the achievement of educational goals, particularly in improving teachers’ professional competence. This study employed a descriptive qualitative research method. Data were collected through observation, interviews, and documentation. The data were then analyzed using data reduction, data display, and data verification techniques. The results of this study indicate that: (1) the principal’s autocratic leadership style is characterized by limited trust given to teachers, as the principal applies a certain degree of coercion in involving teachers in training programs; (2) the principal’s democratic leadership style is reflected in prioritizing coordination, encouraging criticism and suggestions from teachers, providing guidance, opportunities, and full support for teachers to develop their professional competence; and (3) the supporting factors include teachers’ enthusiasm, harmonious relationships between the principal and teachers, and the principal’s strong commitment. Meanwhile, the inhibiting factors consist of the principal’s leadership behavior, inadequate facilities and infrastructure, and the low professional competence of some teachers. Keywords: Leadership Style, Principal, Teacher Professional Competence.